2007
DOI: 10.1063/1.2749717
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and magnetotransport properties of (AlGaN∕GaN):Mg∕(GaMnN) heterostructures at room temperature

Abstract: Dilute magnetic semiconductor films (GaMnN) are highly resistive, making transport measurements difficult to achieve. However, when GaMnN films are sandwiched between p-type doped (AlGaN∕GaN) strained-layer superlattices, holes from the superlattice interact with the Mn3+∕2+ ions and transport measurements were realized. The authors have found also that the ferromagnetic properties of GaMnN critically depend on the level of p-type doping in the superlattice. They report anomalous Hall effect measurements in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…8 The crystal field of the lattice splits the fivefold degenerate d shell of Mn into doublet e and a pseudotriplet t 2 states. [13][14][15] Doping with the shallow Mg acceptor has enhanced carrier-mediated ferromagnetism of GaMnN films. Optical absorption and photoconductivity measurements on GaMnN show deep optical absorption bands at 1.5 and 2.0 eV.…”
mentioning
confidence: 99%
“…8 The crystal field of the lattice splits the fivefold degenerate d shell of Mn into doublet e and a pseudotriplet t 2 states. [13][14][15] Doping with the shallow Mg acceptor has enhanced carrier-mediated ferromagnetism of GaMnN films. Optical absorption and photoconductivity measurements on GaMnN show deep optical absorption bands at 1.5 and 2.0 eV.…”
mentioning
confidence: 99%
“…Our recent results showed that p-type ͑AlGaN/GaN͒ strained-layer superlattices ͑SLSs͒ forming p-SLS/GaMnN/p-SLS heterostructure overcome the problem of the highly resistive GaMnN films. 11 A correlation between the FM of the film and the availability of holes in the p-type SLSs has been observed. Our current approach is based on separating the DMS mediating hole carriers from the GaMnN films by growing GaMnN on a p-GaN layer.…”
mentioning
confidence: 87%
“…Our current approach is based on separating the DMS mediating hole carriers from the GaMnN films by growing GaMnN on a p-GaN layer. 10,11 The source of mediating carriers is the p-GaN and the hole concentration can be controlled by applying an electric field.…”
mentioning
confidence: 99%
“…This may be achieved by substitutional doping of double valent Mg Ga in the GaN spacer, as the carrier-mediated antiferromagnetic IEC in the DMS superlattices and multilayers discussed earlier by Jungwirth et al 9 For this reason, we calculated the IEC between two (Ga, Cr)N layers separated by the Mgdoped GaN spacer, where the Mg doping in the spacer is known to increase the hole concentrations directly in the GaN layers. 28 Fig . 2 presents the calculated IECs for the (Ga, Cr)N multilayers with one Mg atom doped into the middle of the GaN spacer layers (Fig.…”
Section: B Effect Of Mg Dopingmentioning
confidence: 99%